Analysis of Factors Affecting Economic Growth in the Bengkulu Coastal Area - Rifdah Mahdiyah Rahmah; Barika Barika (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This research aims to analyze the factors that influence economic growth in the Bengkulu coastal area. The type of research is quantitative-descriptive. This research uses secondary data in the form of panel data, which is a combination of time series data for 2012–2021 and cross-section data consisting of the districts of North Bengkulu, South Bengkulu, Kaur, Seluma, Muko-Muko, Central Bengkulu, and Bengkulu City. Data sourced from the Bengkulu Province Central Statistics Agency includes data on economic growth, human development index, Gini ratio, and industrial sector employment. The results of panel data regression analysis show that the variables human development index, Gini ratio, and number of workers in the industrial sector have a significant influence on economic growth in the coastal areas of Bengkulu province, with an R2 value of 41%, while the remaining 59% is influenced by other variables outside the model.